Soursop Leaves (Annona muricata Folium) on Mice (Mus musculus) Fetus - Yunita Suryani; Truly Deti Rose Sitorus; Setyorini Irianti (Althea Medical Journal, 2014)
Background: Soursop leaf ethanol extract (Annona muricata (L) Folium) contains acetogenins which are cytotoxic and have the ability to halt cell growth. This study aimed to understand whether acetogenins have teratogenic effects on mice fetus (Mus musculus).Methods: This study was performed at the Pharmacology and Therapy Laboratory of the Faculty of Medicine, Universitas Padjadjaran, Bandung, between October and November 2012. The study  was an experimental laboratory study  utilizing 27 pregnant mice which were divided into 3 groups. The first group was the negative control, the second was given soursop leaf ethanol extract at pre-implantation phase (day 1 to 5) and the third had the extract provided in the organogenesis phase (day 6 to 15). Laparotomy was performed on the 19th day of pregnancy. The parameters used were the number of implantation, the number of live and dead or resorbed fetus, the weight and length of the fetus, as well as the macroscopic external morphology abnormalities. The data gained from test subjects were compared to those of the control group. The statistical test used was the normality tes with the Kolmogorov-Smirnov method which was then followed by T-test or Mann-Whitney statistical tests.Results: The experiment exhibited significant differences in the weight and length of the fetus (p-value 0.000), proving that soursop leaf ethanol extract could inhibit intrauterine growth. Aside from that, external morphological abnormalities such as hemorrhage on the head, face, neck, back, forelimbs, hindlimbs, and microcephaly were also found.Conclusion: The soursop leaf ethanol extract (Annona muricata (L) Folium) has a teratogenic effect on mouse (Mus musculus) fetus. [AMJ.2014;1(1):48–53]Key words: Acetogenins, Soursop leaf ethanol extract, TeratogenicEfek Teratogenik Ekstrak Etanol Daun Sirsak (Annona muricata Folium) terhadap Fetus Mencit (Mus musculus) Latar belakang: Ekstrak etanol daun sirsak (Annona muricata Folium) mengandung senyawa aktif Acetogenins yang bersifat sitotoksik atau dapat menghambat pertumbuhan sel. Penelitian ini dilakukan untuk mengetahui efek teratogenik Acetogenins terhadap fetus mencit (Mus musculus).Metode: Penelitian ini dilakukan di Laboratorium Farmakologi dan Terapi Fakultas Kedokteran Universitas Padjadaran periode Oktober–November 2012. Penelitian bersifat eksperimental laboratorik dengan metode sampel acak menggunakan 27 ekor mencit hamil yang dibagi dalam 3 kelompok. Kelompok 1 sebagai kontrol negatif, kelompok 2 diberikan ekstrak etanol daun sirsak pada masa praimplantasi (hari ke-1 sampai ke-5), dan kelompok 3 menerima ekstrak pada masa organogenesis (hari ke-6 sampai ke-15). Laparotomi dilakukan pada hari ke-19 kehamilan. Parameter yang digunakan berupa jumlah hasil implantasi, jumlah fetus hidup, jumlah fetus mati atau resorbsi, berat dan panjang badan fetus, serta abnormalitas morfologi eksternal fetus yang dinilai secara makroskopis. Data yang didapat pada kelompok perlakuan dibandingkan dengan kelompok kontrol. Uji statistik yang digunakan adalah uji normalitas data dengan uji Kolmogorov-Smirnov dan dilanjutkan dengan uji T- atau Mann-Whitney.Hasil: Hasil penelitian menunjukkan perbedaan signifikan pada berat dan panjang fetus mencit (nilai p 0,000), sehingga ekstrak etanol daun sirsak terbukti menghambat pertumbuhan intrauteri. Selain itu ditemukan juga kelainan morfologi eksternal seperti perdarahan pada kepala, wajah, leher, punggung, tangan, kaki, dan mikrosefali.Simpulan: Ekstrak etanol daun sirsak (Annona muricata Folium) memiliki efek teratogenik terhadap fetus mencit (Mus musculus).Kata kunci: Acetogenins, ekstrak etanol daun sirsak, teratogenik DOI: 10.15850/amj.v1n1.297